HIV Status and Contraceptive Utilization among Women in Cameroon. (18th February 2019) - Budhwani, Henna; Hearld, Kristine Ria; Dionne-Odom, Jodie; Manga, Simon; Nulah, Kathleen; Khan, Michelle; Welty, Thomas; Welty, Edith; Tita, Alan Thevenet
Objective: We examined patterns of contraceptive utilization by HIV status among women in Cameroon, hypothesizing that women living with HIV would utilize contraception at higher rates than their HIV-negative peers. Methods: Deidentified, clinical data from the Cameroon Baptist Convention Health Services (2007-2013) were analyzed (N = 8995). Frequencies compared outcomes between women living with HIV (15.1%) and uninfected women. Multivariate analyses examined associates of contraceptive utilization and desire to become pregnant. Results: Contraceptive utilization was associated with higher education, living with HIV, monogamy, and higher parity ( P < .001). Women living with HIV had 66% higher odds of using contraceptives than their negative peers (odds ratio [OR]: 1.66, confidence interval [CI]: 1.45-1.91, P < .001). Polygamous women had 37% lower odds of using contraceptives compared to monogamous women (OR: 0.63, 95% CI: 0.52-0.75, P < .001). Conclusion: Increasing contraceptive utilization in resource-constrained settings should be a priority for clinicians and researchers. Doing so could improve population health by reducing HIV transmission between partners and from mother to child.